Pengaruh Media Pembelajaran Interaktif Berbasis Android Berbantuan Ispring Suite 11 terhadap Hasil Belajar Siswa Kelas X SMK Auto Matsuda (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the impact of Android-based interactive learning media supported by iSpring Suite 11 on students’ learning outcomes in Grade X Informatics at SMK Auto Matsuda. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed. The sample involved 43 students: 20 in the control class (X TKRO 1) using conventional methods and 23 in the experimental class (X TKJ 2) using interactive media. Data were collected through pretest and posttest instruments and analyzed using an independent sample t-test to determine the significance of the differences between groups. The results indicated an improvement in the experimental group’s average score from 74.35 to 84.35, while the control group’s score increased from 59.50 to 64.50. The t-test showed a significant difference between the two groups (t = -4.630, p < 0.05; Sig. = 0.000). These findings suggest that Android-based interactive media, with support from iSpring Suite 11, is effective in enhancing student learning outcomes, particularly in the topic of computer hardware